Anti-Hyperuricemic and Nephroprotective Effects of Rhein in Hyperuricemic Mice - Meng, Zhaoqing; Yan, Yunxia; Tang, Zhaohui; Guo, Changrun; Li, Na; Huang, Wenzhe; Ding, Gang; Wang, Zhenzhong; Xiao, Wei; Yang, Zhonglin (Planta Medica, 2015)
Hyperuricemia has been considered to be a key risk factor for kidney disease. The formation of uric acid crystals in the kidney further stimulates an intensive inflammatory response. Rhein possesses various pharmacological activities, including anti-inflammatory, antioxidative, antitumor, purgative effects, and so on. To our knowledge, no previous work has been reported about the therapeutic effect of rhein on urate nephropathy. In this study, a model of hyperuricemia and nephropathy induced by adenine and ethambutol in mice was established. Meanwhile, the potential beneficial effects and mechanisms of rhein on hyperuricemia and nephropathy were also investigated. The results demonstrated that rhein significantly decreased the serum uric acid level by inhibiting the xanthine oxidase activity and increasing the excretion of urinary uric acid. In addition, rhein also markedly improved kidney damage related to hyperuricemia. Further investigation indicated that rhein improved the symptoms of nephropathy through decreasing the production of proinflammatory cytokines, including interleukin 1β, prostaglandin E2, and tumor necrosis factor-α and inhibiting the expression of transforming growth factor-β1. The present study suggests that rhein may have a considerable potential for development as an anti-hyperuricemic and nephroprotective agent for clinical application.
Keywords: rhein; hyperuricemia; nephroprotective effect; xanthine oxidase; uricosuric action; interleukin-1β; transforming growth factor-β1